Urban water systems in India: A way forward - Mihir Shah (Indian Council for Research on International Economic Relations (ICRIER), 2016)
Urban water and wastewater management are relatively under-studied subjects in India. The Indian urban space has been understood in an undifferentiated manner, which ignores the specificities deriving from the stage of urban development, the sources of water, as also the diverse nature of aquifers characterizing urban settlements. This paper provides a new presentation of the urban water problem and offers a set of solutions that are sustainable, both in ecological and financial terms, and seek to tackle the deep inequities in the urban water space in India. It highlights the significance of groundwater, the dark spot of Indian urban water planning and proposes a typology that could be used to comprehend the diversity of urban aquifer formations. The paper highlights the urban wastewater challenge and emphasises the need to work simultaneously on water and wastewater management. The paper advances a series of hypotheses, an initial analytical framework and the outlines of a way forward for urban water systems in India, which could provide a rich terrain for further research. The paper concludes with brief illustrative case-studies of two major emerging cities - Indore and Nagpur - where the new approach advocated in the paper could be fruitfully tried out.
Keywords: Q; 330; aquifers; wastewater treatment; recycling; water distribution; PPP